Evaluation of some Mango Interstock on Kiet Scion Growth - Ismail, Omayma M.; Ebeed, Sanaa (JOURNAL OF ADVANCES IN BIOLOGY, 2013)
This experiment was carried out during the years 2009-2011 to investigate the effect of the mangointerstock on growth Kiet scion also their effect on sukkary rootstock. The rootstock plants were grafted with scion Hindi, Ewais, Seddik and Kiet as the first grafting , after one year the second graft were done by Kiet scion on the different interstock. The vegetative growth parameters as length cm, thickness mm, leaves number, leaf area cm2 and fresh dry weight of shoots (g) were recorded. The results cleared that the rootstock length of sukkary had the highest value (43.95 and 43.80 cm) with Kiet and Seddik scion respectively. The scion length was insignificant differences among Hindi, Ewais and Seddik where the lowest scion length wasKiet 57.25cm. The rootstock and scion thickness were insignificant among all of them. The means of leaves number were ranged from 31.10 to 47.80 of Hindi and Kiet respectively and the leaf area was the highest of Hindi 113.4 cm2 and the lowest one of Kiet 45.04 cm2 .The data of second grafting, where the Kiet scion length was the highest value 79.50 cm., also the Kiet interstock and the Kiet scion thickness were the highest values 1.20 and 1.12 cm respectively but the Hindi interstock and the Kiet scion were insignificant values 1.14 and 1.01 cm respectively.. The means of Kiet leaves number ranged from 23.8 to 44.30 of Ewais and Kiet interstock respectively. The Kiet scion of Hindi interstock had the highest significant values of shoots fresh and dry weight 214.4 and 102.1 g. respectively, while Kiet interstock was the lowest significant values of shoots fresh and dry weight (67.90 and 30.27 g.) respectively.These results revealed that the Kiet interstock had a dwarfing effect while the Hindi had an activating effect followed by Seddik then Ewais